OPTIMALISASI SISTEM KEAMANAN DATA UNTUK JENIS FILE DOKUMEN MENGGUNAKAN TEKNIK STEGANOGRAFI END OF FILE, ALGORITMA KRIPTOGRAFI RIVEST CODE 6, DAN ALGORITMA KOMPRESI HUFFMAN - Mochammad Nauval Rifkiansyah (2021)
Security and confidentiality of data is an important aspect in the field of communication, especially communication using computer media. Data security processes that are widely circulated include using cryptography, steganography and compression. Making this application uses a combination of three algorithms, namely cryptography which is a mathematical study that has a relationship with information security aspects such as data integration, entity authenticity, and data authenticity. The cryptographic method that will be used is the Rivest Code 6 algorithm. Apart from file security issues, size or size issues must also be considered because most files that have gone through the locking process become larger in size than the file. Therefore, the author also uses the Huffman compression method which makes the file size minimized after the file is locked in this file security cryptography application. The last combination in the method used is steganography, where steganography is widely used to send a message without being noticed by others by using digital media in the form of image files. The method used in this steganography is the End Of File method where file insertion is done at the end of the image that is the place for insertion. The results of this study state that combining the three algorithms can maintain confidentiality and not damage the contents of the information contained in the data. In addition, there will be an increase in file size after data locking, where an increase in the size of the file resulting from the locking process occurs depending on the size of the secret data and container file.